Genetic association between immune-mediated inflammatory diseases and peripheral artery disease: a Mendelian randomization study - Haichao Wu; Dandan Zheng; Long Zhou; Qiang Wang; Tao Wang; Siyuan Liang (Scientific Reports)
Abstract Several observational studies have revealed that immune-mediated inflammatory diseases (IMIDs) are associated with an increased risk of peripheral artery disease (PAD). However, the causal association remains to be determined. To corroborate previous research, we conducted Mendelian randomization (MR) analysis with the aim of clarifying the associations of various IMIDs with PAD. two-sample MR analysis was conducted to investigate the potential causal association between eight common IMIDs (including rheumatoid arthritis (RA), Crohn’s disease (CD), ulcerative colitis (UC), systemic lupus erythematosus (SLE), ankylosing spondylitis(AS), psoriasis(PSO), multiple sclerosis(MS), and hashimoto thyroiditis(HT)) and PAD. Genome-wide association study (GWAS) was used to identify genetic variants associated with IMIDs and PAD. We employed the inverse variance weighted (IVW) method as the primary method to verify the causal relationship between exposures (IMIDs) and outcomes (PAD). In addition, heterogeneity test, horizontal pleiotropy test, and leave-one-out analysis were performed to evaluate the robustness of the MR results. The IVW model yielded evidence of a positive association between RA and PAD (OR = 1.059, 95% CI: 1.026–1.094, p<0.001), which was consistent with the results obtained from MR-Egger regression and weighted median analyses, indicating that the results of MR analysis were reliable. However, no statistically significant associations were observed between other IMIDs, including UC, CD, SLE, AS, PSO, MS, and HT, and PAD. Our analysis supported the causal association of RA with increased risks of PAD. Strengthening screening and prevention of PAD is of great significance in reducing the risk of PAD in populations with RA.